Production and characterization of yeasts grown on media composed of spruce-derived sugars and protein hydrolysates from chicken by-products - Lapeña, David (Microb Cell Fact, 2020)
BACKGROUND: A possible future shortage of feed protein will force mankind to explore alternative protein sources that can replace conventional soymeal or fishmeal. Several large industrial organic side-streams could potentially be upgraded to feed protein using a fermentation process to generate single cell protein. Yeast is the most widely accepted microorganism for production of single cell protein, because of its superior nutritional quality and acceptability among consumers. Here, we have assessed the growth of four different yeasts, Cyberlindnera jadinii, Wickerhamomyces anomalus, Blastobotrys adeninivorans and Thermosacc(®) Dry (Saccharomyces cerevisiae), on media composed of enzymatically saccharified sulfite-pulped spruce wood and hydrolysates of by-products from chicken, and we have characterized the resulting yeast biomass. RESULTS: Generally, the yeast grew very well on the spruce- and chicken-based medium, with typical yields amounting to 0.4–0.5 g of cell dry weight and 0.2–0.3 g of protein per g of sugar. B. adeninivorans stood out as the most versatile yeast in terms of nutrient consumption and in this case yields were as high as 0.9 g cells and 0.5 g protein per g of sugar. The next best performing yeast in terms of yield was W. anomalus with up to 0.6 g cells and 0.3 g protein per g sugar. Comparative compositional analyses of the yeasts revealed favorable amino acid profiles that were similar to the profiles of soymeal, and even more so, fish meal, especially for essential amino acids. CONCLUSIONS: The efficient conversion of industrial biomass streams to yeast biomass demonstrated in this study opens new avenues towards better valorization of these streams and development of sustainable feed ingredients. Furthermore, we conclude that production of W. anomalus or B. adeninivorans on this promising renewable medium may be potentially more efficient than production of the well-known feed ingredient C. jadinii. Further research should focus on medium optimization, development of semi-continuous and continues fermentation protocols and exploration of downstream processing methods that are beneficial for the nutritional values of the yeast for animal feed.